2000
DOI: 10.1093/nar/28.2.527
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific binding of Taz1p dimers to fission yeast telomeric DNA

Abstract: The fission yeast (Schizosaccharomyces pombe) taz1 gene encodes a telomere-associated protein. It contains a single copy of a Myb-like motif termed the telobox that is also found in the human telomere binding proteins TRF1 and TRF2, and Tbf1p, a protein that binds to sequences found within the sub-telomeric regions of budding yeast (Saccharomyces cerevisiae) chromosomes. Taz1p was synthesised in vitro and shown to bind to a fission yeast telomeric DNA fragment in a sequence specific manner that required the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 33 publications
(50 reference statements)
2
48
2
1
Order By: Relevance
“…Given that Taz1 binds to telomeric DNAs as a homodimer [15], our data suggest that dimerization of Taz1 is likely mediated by another region outside of Taz1 HD . Various fragments were evaluated for their ability to form a homodimer in solution by gel filtration chromatography and chemical cross-linking analyses (Supplementary information, Figure S1I).…”
Section: Dear Editormentioning
confidence: 80%
See 1 more Smart Citation
“…Given that Taz1 binds to telomeric DNAs as a homodimer [15], our data suggest that dimerization of Taz1 is likely mediated by another region outside of Taz1 HD . Various fragments were evaluated for their ability to form a homodimer in solution by gel filtration chromatography and chemical cross-linking analyses (Supplementary information, Figure S1I).…”
Section: Dear Editormentioning
confidence: 80%
“…Since Taz1 exists as a homodimer [15] ( Figure 1G), and each monomer contains only one Myb domain, we hypothesized that Taz1 homodimerization is also essential for its telomere association. To test this hypothesis, the L445R mutation that disrupts the Taz1 dimerization in yeast two-hybrid assay was analyzed for its effect on the DNA binding ability of Taz1 by electrophoretic mobility shift assay (EMSA).…”
Section: Dear Editormentioning
confidence: 99%
“…Recently, it has been shown that the isolated Myb-like domain of TRF1 binds specifically and with significant affinity to telomeric DNA as a monomer (20). Although with less specificity than the full-length dimer, the isolated Myb-like domain of Taz1p was also capable of sequence-specific DNA binding (23,24). Taken together, these results indicate that the Myblike domain is indeed responsible for specific telomeric DNA recognition.…”
mentioning
confidence: 85%
“…Although full-length TRF1 and Taz1p bind to DNA as a preformed homodimer, the isolated Myb-like domains of these proteins were capable of sequence specific binding as a monomer (20,23). To examine whether the isolated Myb-like domain of RTBP1 is active as a monomer, RTBP1-(506 -615) was fused to the 28-kDa glutathione S-transferase (GST) protein.…”
Section: Myb-like Domain Of Rtbp1 Binds Telomeric Repeat Dnamentioning
confidence: 99%
See 1 more Smart Citation